Rumah Produksi Pupuk Organik di Senduro, Lumajang - Ekayanti, Putu; Trimarianto, Ciptadi; Agusintadewi, Ni Ketut (Jurnal Arsitektur Universitas Udayana, 2022)
The agriculture and livestock sector in Senduro District is very abundant because this area has an area of ????approximately 13,000 hectares of agricultural land and the cultivation of various livestock animals. The local government is trying to develop agriculture towards organic farming and maximize the potential of livestock waste to be produced into organic fertilizer locally. The design and planning of the Organic Fertilizer Production House in Senduro aim to provide local organic fertilizer processing facilities that are environmentally friendly and able to overcome the impact of environmental damage due to livestock waste pollution. Through a function, activity, and community approach by applying the concept of environmentally friendly buildings and paying attention to environmental aspects, it is possible to produce a building mass design that takes into account the contours, production process flow, mass patterns, and circulation of buildings that are sensitive to the environment. The realization of the appearance of the building by emphasizing environmentally friendly principles is support by the use of local materials, such as non-combustible bricks, steel, bamboo, which are used in the facade of the building.